Implementation of the FIFA 11+ injury prevention program by high school athletic teams did not reduce lower extremity injuries: A cluster randomized controlled trial - Slauterbeck, J. R.; Choquette, R.; Tourville, T. W.; Krug, M.; Mandelbaum, B. R.; Vacek, P.; Beynnon, B. D. (The American Journal of Sports Medicine, 2019)
Background: Lower extremity injuries are common in high school sports and are costly, and some have poor outcomes. The FIFA 11+ injury prevention program has been shown to decrease injuries in elite athletes by up to 72%. Hypothesis: High schools in which coaches implement the FIFA 11+ injury prevention program in their athletic programs will have a decreased incidence of lower extremity injuries compared with schools using their usual prepractice warm-up. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Fourteen high schools that employed an athletic trainer were randomly assigned to either the FIFA 11+ group or control group (usual warm-up routine). Exposure to sports and injuries were recorded and used to determine the incidence rates of lower extremity injuries per athlete-exposure (AE). The FIFA 11+ program was implemented by coaches and complicance with the program recorded. Results: There were 196 lower extremity injuries among 1825 athletes in the FIFA 11+ group and 172 injuries among 1786 athletes in the control group (1.59 and 1.47 injuries per 1000 AEs, respectively; P = .771). The distribution of the types of injury in the 2 groups did not differ, but the body locations where the injuries occurred differed somewhat (P = .051). The FIFA 11+ group had larger proportions of thigh and foot injuries, while the control group had higher proportions of knee and ankle injuries. Group differences in injury rates varied with sport (P = .041 for interaction), but there were no significant differences in injury rates between the FIFA 11+ and control groups by sport, level of play, and sex. In the FIFA 11+ group, 62% of the coaches reported that their teams completed the full FIFA 11+ program at least once a week, and 32% reported that they completed it at least twice a week. Conclusion: This study did not demonstrate a reduction in lower extremity injuries in schools randomized to use the FIFA 11+ program compared with schools using their usual prepractice warm-up program. Coach-reported compliance with performing the FIFA 11+ program at least twice a week was low.